Benson Relaxation Technique to Reduce Anxiety in Inpatients: A Case Study - Emilia, Ni Luh; Herman, Fadila; Restawan, I Gede (An Idea Health Journal, 2025)
Background: Anxiety is a common psychological condition often experienced by inpatients due to changes in health status, unfamiliar environments, and uncertainty about treatment. If left untreated, anxiety can lead to various negative outcomes, including increased blood pressure, sleep disturbances, and excessive restlessness. One effective non-pharmacological intervention to reduce anxiety is Benson relaxation therapy, which combines deep breathing techniques with the repetition of calming words or prayers. This study aimed to apply Benson relaxation therapy to reduce patient anxiety in the inpatient ward of Woodward Hospital, Palu.Methods: A descriptive case study design with a nursing care approach was employed. The subject of the study was one patient experiencing moderate anxiety. Benson relaxation therapy was administered for four days, twice daily, with each session lasting 10–20 minutes. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Result: The HARS score decreased from 25 (moderate anxiety) to 16 (mild anxiety). The patient also showed improvements in sleep patterns, reduced muscle tension, and alleviation of somatic symptoms such as dizziness and restlessness. Conclusion: Benson relaxation therapy effectively reduces anxiety in hospitalized patients, contributing to the resolution of anxiety-related problems.